Beauty and the beast [videorecording (Blu-ray + DVD)] - Watson, Emma, 1990-; Stevens, Dan, 1982-; Evans, Luke, 1979-; Kline, Kevin; Gad, Josh, 1981-; Leprince de Beaumont, Jeanne-Marie, 1711-1780 (Disney Blu-ray., 2017)
The fantastic journey of Belle, a bright, beautiful, and independent young woman who is taken prisoner by a beast in his castle. Despite her fears, she befriends the castle's enchanted staff and learns to look beyond the Beast's hideous exterior and realize the kind heart and soul of the true Prince within.